Parameter of Compulsory Wills in The Right of Inheritance for Stepchildren: Parameter Wasiat Wajibah dalam Hak Waris Bagi Anak Tiri - Saleh, Farah Labita Putri Insyira Maharani; Sulistyarini, Rachmi; Hidayat, Fitri (Faculty of Law, Universitas Brawijaya, 2025)
This Research examines the parameters that determine whether a stepchild is entitled to an obligatory will (wasiat wajibah) and includes a legal issue—that is, a legal vacuum in the regulation of wasiat wajibah for stepchildren. This legal vacuum is evident from the absence of explicit norms in Presidential Instruction No. 1 of 1991 concerning the Dissemination of the Compilation of Islamic Law (KHI), which opens up the possibility of differing interpretations at the level of the religious courts. Accordingly, the researchers then sought an accurate formulation for determining those parameters using normative juridical research with an approach based on legislation, conceptual analysis, and case studies to observe the evolving materials of parameters in each case where judges apply the parameter in their decisions, grounded in the principles of justice, benevolence (maslahah), legal certainty, legality, and textual-legal foundations.To realize legal certainty while remaining aligned with the principles of legal progressiveness, judges often apply qiyās to the provisions on adopted children by considering the principles of justice, public benefit (maslahah), as well as emotional and caregiving relationships. This dynamic illustrates the efforts of the religious judiciary to maintain legal certainty in harmony with substantive justice. Based on these findings, this study recommends that the Supreme Court, the Ministry of Religious Affairs, and national regulatory bodies promptly establish explicit formal regulations concerning compulsory wills (wasiat wajibah) for stepchildren, either through a revision of the Compilation of Islamic Law (KHI) or through a Supreme Court Circular (SEMA) as a uniform juridical guideline. Such regulations should include objective criteria—such as the duration of caregiving and the degree of emotional closeness—so that judges no longer rely solely on individual interpretation. Accordingly, legal protection for stepchildren can be realized through norms that are clear, definite, and reflective of both justice and public welfare.